PANDANGAN MANG KOKO DALAM BERKESENIAN - Ruswandi, Tardi (Paraguna, 2017)
This study focused Mang Koko in view ofthe arts in general,  the artist,  and the Sundanese karawitan. Mang   Koko   view   of  the   matters   that   will   be   discussed   in   further description.  The purpose is to explain Mang Koko view of the arts and artists.  The method used is a qualitative method. While the results of this study revealed that the views Mang Koko the arts in general, because the art is an ancestral cultural heritage that should be maintained and developed. In everyday life the artist is not enough just good practice,  but also to be godly,  because the artist must have the mental strength,  discipline,  honesty,  and can  avoid  the  things  that  are  negative. Similarly  Sundanese  gamelan,  is  not  only  an essential element in kahidupan artist,  but should be part ofhuman life.